NG2 glia-derived GABA release tunes inhibitory synapses and contributes to stress-induced anxiety - Xiao Zhang (Nature Portfolio, 2021)
Nerve/glial antigen 2 (NG2) glia can sense synaptic inputs from neurons. Here, the authors show NG2 glia form functional GABAergic synapses by regulating inhibitory synaptic transmission onto adjacent hippocampal interneurons, and activation of NG2 glia induces anxiety-like behaviour in a mouse model of chronic social defeat stress.